Internal bracing augmentation of the ulnar collateral ligament on a level 10 competitive gymnast: a case study - Wal, D. V.; Potter, B.; David, S. L.; German, N. (International Journal of Athletic Therapy & Training, 2021)
Ulnar collateral ligament (UCL) injuries have become increasingly more common over the years. Reconstruction and nonoperative treatment have been the conventional treatment for athletes, especially for overhead athletes. This case study presents a 16-year-old female, competitive Level 10 gymnast, with a complete distal tear of her UCL with a full thickness, Grade 3, ulnar sided avulsion off of the sublime tubercle. She underwent medial UCL repair with internal brace augmentation with the goal of faster return to gymnastics. To the author`s knowledge, this is the second gymnast reported in the literature to have an internal brace augmentation completed on the UCL.